PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE RECIPROCAL TEACHING BERBANTUAN MEDIA KOTAK KARTU MISTERI (KOKAMI) DALAM MENINGKATKAN MOTIVASI BELAJAR SEJARAH SISWA KELAS X IPS 2 MAN ACEH SINGKIL - Aidil Fitriadi (Riwayat: Educational Journal of History and Humanities, 2018)
This article is entitled “Application of Reciprocal Teaching Type Cooperative Learning Model Assisted by Kokami Media in Increasing Students' Motivation to Learn History in Class X IPS 2 MAN Aceh Singkil. The background of the problem in this research is the lack of motivation to learn by students on the subject of history. This study aims to determine the application of the Kokami media-assisted reciprocal teaching learning model in class X IPS 2 MAN Aceh Singkil and to determine the application of the Kokami media-assisted reciprocal teaching learning model in increasing the motivation to learn history of students in class X IPS 2 MAN Aceh Singkil. This type of research uses a qualitative approach with a descriptive qualitative research type. The subjects used in this study were class X IPS 2 with 20 students consisting of 7 male students and 13 female students. The data collection technique used is using observation sheets as well as documentation. The results of observing student activities in the implementation of learning are 80% with good categories. The students' motivation in applying the reciprocal teaching learning model assisted by Kokami media is 96.5% in the very good category.